If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(2x + -2) + 2x = -32 Reorder the terms: -2(-2 + 2x) + 2x = -32 (-2 * -2 + 2x * -2) + 2x = -32 (4 + -4x) + 2x = -32 Combine like terms: -4x + 2x = -2x 4 + -2x = -32 Solving 4 + -2x = -32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -2x = -32 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -32 + -4 -2x = -32 + -4 Combine like terms: -32 + -4 = -36 -2x = -36 Divide each side by '-2'. x = 18 Simplifying x = 18
| x^3-10x^2+x-2015=0 | | 3(y-10)+1=-1.925(y-8) | | 1-6x+3x=31 | | 14-(x+4.7)=3(x+9)-10 | | 3x^4-8x^3-18x^2+12=0 | | 0.5x^2=68 | | 34x+12xy+12y= | | (5y-9)(-9y^2-y+6)= | | x=3*4-8*x | | 2*3.14x=94.2 | | 5x+10y=-25 | | x(x-12)(x+11)=0 | | -5-x=2-(4x+6) | | 3x-4=-9x+68 | | -n^2+2n= | | (3x-15)(x+10)=0 | | 2x=13y+5 | | 2x+17=4x-4 | | n^2+2n=80 | | (4x-32)(x+5)=0 | | -5600.00+2000.00=-2800 | | x(x-11)(x+10)=0 | | Y=9xsquared+7 | | 2f-3f+9g+2f-2f+f= | | 5g+(2+4h-2g)-(4g+2h+3)= | | 30700=50e^3t | | Xy+2x+3y=11 | | (2x-3)(2x-3)+5x=(x-3)*(4x+11) | | 2y+2x=100 | | (3+5i)-(5-3i)= | | 9p-4q+11p+7q= | | a+a-3b+2b= |